Perceptions of the minimum wage in the Johannesburg taxi industry - Tumelo, Sechaba (My University, 2017)
Minimum wage laws in South Africa have been enacted and implemented for some time with a broader intention that purports to protect and regulate what are categorized at least from state’s definition as the vulnerable sectors, which includes the taxi industry. The minibus taxi industry in South Africa is characterized and plagued by inherent exploitative labour relations between taxi drivers and operators. There are often contrasting views and disagreement on the minimum wage which is supposed to be implemented by the Department of Labour as the custodian of all the labour laws in the country through inspections and enforcement by labour inspectors. The purpose of this study was to investigate the perceptions held by the various stakeholders in the taxi industry with respect to the implementation of the Sectoral Wage Determination 11 as provided for by the Basic Conditions of Employment Act, of1997. Interviews were held with ten taxi drivers, ten taxi operators based in Johannesburg and from the Department of Labour, and three team leaders in the Inspection and Enforcement Services, all based and servicing Johannesburg. The study established that there is enough knowledge and appreciation of the minimum wage; however, there is to a large extent transgressions and noncompliance from employers in the industry. Monitoring and enforcement remain a challenge fuelled by peculiarities and the dynamism that is not in tandem with industry realities and legislative prescripts.
Research Report submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand in partial fulfilment for a Masters in Management in the field of Public and Development Management. February 2017
Keywords: Minimum wage--Law and legislation--South Africa; Wages--South Africa; Taxicabs--South Africa